Cryptic diversity in non-geniculate coralline algae: a new genus Roseolithon (Hapalidiales, Rhodophyta) and seven new species from the Western Atlantic. Issue 2 (3rd April 2022) - Miranda Coutinho, Luana; Penelas Gomes, Fernanda; Nasri Sissini, Marina; Vieira-Pinto, Talita; Muller de Oliveira Henriques, Maria Carolina; Oliveira, Mariana Cabral; Antunes Horta, Paulo; Barbosa de Barros Barreto, Maria Beatriz
ABSTRACT: Molecular studies have revealed cryptic diversity and polyphyly in the genus Lithothamnion . In this study we aimed to investigate the diversity and phylogeny of specimens that are morphologically described as Lithothamnion based on extensive collections along the Brazilian coast and an integrative taxonomic approach. Our results led to the proposal of Roseolithon gen. nov. belonging to the subfamily Melobesioideae. This new genus is described from the tropical north-western Atlantic and warm temperate south-western Atlantic specimens, based on phylogenetic analyses of psb A, rbc L-3P, COI-5P and SSU rDNA molecular markers, species delimitation methods, genetic divergence and morpho-anatomical observations. The integrative approach led us to find a set of morphological features that characterize Roseolithon : (i) thallus organization monomerous with plumose hypothallus (non-coaxial); (ii) flared epithallial cells; (iii) subepithallial cells varying in size and may be shorter, approximately equal to or longer than those subtending them; (iv) cells of adjacent filaments linked by fusions; (v) tetra/bisporangial conceptacle chambers multiporate; and (vi) the presence of pore canals bordered by rosette cells in depressions giving the surface a pitted appearance. Depending on the species, this pitted appearance occurs due to the sunken or disintegrated rosette cell roofs. The grade of the degeneration of the rosette cell roofs characterizes the species of this genus. The new genus Roseolithon is composed of at least 18 species, of which we describe seven new species: Roseolithon tupii, R. tamoioi, R. tremembei, R. potiguarae, R. karaiborum, R. purii and R. goytacae. Highlights Phylogenetic analyses revealed Lithothamnion to be a polyFphyletic genus. Integrative taxonomy enabled the description of a new genus Roseolithon. Morpho-anatomy does not reflect molecular phylogeny of non-geniculate coralline algae.